EXISTING PROBLEMS IN REDUCING TAX ARREARS IN ELECTRIC POWER ENTERPRISES - Axmedov Ashrafjon Axadovich (Ecominds Press, 2026)
This article analyzes the existing problems in reducing tax arrears in electric power enterprises. Particular attention is paid to issues related to financial stability, payment discipline, tariff policy, the high level of accounts receivable, and the effectiveness of tax administration mechanisms. The study also examines factors hindering the timely fulfillment of tax obligations, including rising costs of electricity production and supply, delays in payments, and imbalances between revenues and expenses. Based on the analysis, organizational and economic measures, as well as practical recommendations, are proposed to reduce tax arrears and improve the financial sustainability of electric power enterprises.
Keywords: Electric power enterprises, tax arrears, financial stability, tax administration, accounts receivable, tariff policy, payment discipline.